A Survey Study of English Writing Strategies Used by Thai Undergraduates in Business English Program - Arena Jaitrong; Maylaya Kaewsud; Wasinee Kwanthong; Apinya Manochphinyo (Jurnal Bahasa Inggris Terapan, 2022)
The research study aims to explore writing strategies used by Thai first to fourth-year university students. Thirty-six (36) students from the Business English program at a government university in Southern Thailand who had experience in English writing, served as the subject of the research. They responded to a questionnaire. The online questionnaire was created by using SurveyCan. The questionnaire focused on students’ English writing experiences through the use of writing strategies. The results revealed that most of the students used both cognitive strategies and metacognitive strategies for the prewriting or planning stage. During the drafting stage, it was found that most of the students used metacognitive strategies in developing their ideas when writing a text. Besides, they used cognitive strategies and socio-affective strategies in engaging their writing tasks, searching for more information from other resources, and asking their peers. In the post-writing stage, most of the students sometimes used cognitive strategies, metacognitive strategies, and socio-affective strategies, respectively. The findings of this study suggest that most of the students may not get familiar with learning new things from each other in developing their ideas, using critical thinking, and solving problems in their writing. Overall, they use various strategies in each stage of their writing and they may not be aware of the effectiveness of writing strategies in developing their English writing skills at higher levels.